A associação de haloperidol, dexametasona e ondansetrona reduz náusea e vômito no pós-operatório de pacientes obesos, submetidos à gastrectomia vertical laparoscópica : estudo clínico, aleatorizado, controlado e duplamente encoberto - Benevides, Márcio Luiz (2012)
Laparoscopic bariatric surgery is associated with increase of postoperative nausea and vomiting (PONV). The hypothesis of this study was that the combination of haloperidol, dexamethasone, and ondansetron may reduce PONV. Objective: To compare the efficacy of three regimens for antiemetic prophylaxis in patients submitted to laparoscopic sleeve gastrectomy (LSG). Method: A clinical, randomized, controlled, double-blind study was performed in 90 patients with body mass index ≥ 35 kg/m2 , of both genders, submitted to LSG. The patients were divided into three groups: Group O (n=30): ondansetron 8 mg before the end of surgery (BES), Group DO (n=30): ondansetron 8 mg BES and dexamethasone 8 mg at induction of anesthesia (IA) and Group HDO (n=30): ondansetron 8 mg BES, dexamethasone 8 mg and haloperidol 2 mg in IA. We have evaluated the occurrence and intensity of nausea, vomiting, the rescue antiemetic use, pain intensity, the morphine consumption and drugs side effects in 0-2, 2-12, 24- 36 and 0-36 hours (h) postoperative (PO) period. The volume of fluid infused during the hospital stay and length of hospital stay were also evaluated. Results: There was no difference between groups regarding demographic variables, ASA physical status, Apfel score, comorbidities, surgical team, the volume of fluids infused during surgery and the length of preoperative fasting, duration of anesthesia and duration of postanesthesia care unit stay. As for the main clinical outcomes, the incidence of nausea was lower in the Group HDO as compared to Group O (23.7% versus 56.7%, p=0.016) in the period of 0-2 h, in the Group HDO (23.3%) and in the Group DO (26.7%) compared to the Group O (60%) (p=0.008 and p=0.009 respectively) within 12-24 h, and also the incidence of nausea was lower in the Group HDO in relation to the Group O (53.3 versus 86.7 %, p=0.013) in the period 0- 36 h PO. The Group HDO presented lower incidence of vomiting than the Group O (20% versus 53.3%, p=0.015) in the period 0-36 h. The intensity of nausea was less in the Group HDO than in the Group O (p=0.001). The time to first rescue antiemetic administration was higher in the Group HDO compared to the Group O (p=0.006). Moreover, the number of rescues used in the Group HDO was two times less than in the Group O (p=0.002). Regarding secondary outcomes, there was less intensity of pain in the Group HDO when compared to the Group O (p=0.046) and less consumption of morphine in Group HDO than in Group O (p=0.007) and in Group DO (p=0,01). The volume of fluids administered in the PO period in Group O was approximately 1 liter greater than in the Group HDO (p=0.026). Length of stay and adverse events were similar between groups. Conclusion: The combination of haloperidol, dexamethasone and ondanseron promoted reduction of PONV, increased time to first administration of rescue antiemetic and reduced amount of them. Reduced also the pain intensity, the morphine consumption and the volume of fluids infused in the postoperative period of pacientes undergoing LSG.